Anthropometry and Liver Function Parameters in Individuals with Metabolic Syndrome - Aladejana, Adebowale Emmanuel; Aladejana, Elizabeth Bosede (Journal of Pharmacy and Nutrition Sciences, 2021)
Metabolic syndrome (MS) is a metabolic condition commonly associated with central adiposity and altered liver function parameters (LFPs). Several studies have suggested these altered LFPs as a result of fatty liver diseases (e.g., non-alcoholic fatty liver diseases) often prevalent in MS. Since altered LFPs are very common in MS, there is a possibility they can be used as predictors of MS. However, only a few studies have been carried out to evaluate this possibility. This study, therefore, aimed to evaluate the potential of LFPs as predictors or risk factors of MS. The study groups included 50 individuals diagnosed with MS (case group) and 50 apparently normal individuals (control) from Ibadan, Oyo State, Nigeria. Anthropometric measurements, phlebotomy, liver function tests, and lipid profile estimations were done using standard procedures. (The result and conclusion section has been omitted).